Determinants of Cumulative GPA of First Year Widyatama University Students - Nursjanti, Farida; Taruna, Indra; ., Shinta (International Journal of Engineering and Technology, 2018)
As a private college-oriented quality, Widyatama University has some quality commitments including receiving potential prospective students and giving priority to customer satisfaction. However, the university only uses entrance exam score, does not use previous academic performance such as national exam score to select potential prospective students. The aims of this research were to examine and to evaluate the factors which affect students’ First Year Cumulative GPA (FYCGPA) in Widyatama University. This research also investigated the determinants of students’ FYCGPA by the factors to explain variances in FYCGPA. This research used gender, major in high school, national exam score and entrance exam score as independent variables. Stepwise multiple regression analysis was carried out in this study. The result indicated that gender, entrance exam score, and major in high school have significant effect to FYCGPA. The model used in this study showed that 24.6% of the variances in FYCGPA can be explained by gender, entrance exam score, and major in high school. This results show that Widyatama University should consider more factors in selecting potential prospective students and providing services to first year students.